1997
DOI: 10.1074/jbc.272.25.15986
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Phospholipase D by Clathrin Assembly Protein 3 (AP3)

Abstract: 15980 -15985), synaptojanin is identified as a protein that inhibits phospholipase D (PLD) activity stimulated by ADP-ribosylation factor and phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ). Here, the purification from rat brain cytosol of another PLD-inhibitory protein that is immunologically distinct from synaptojanin is described, and this protein is identified as clathrin assembly protein 3 (AP3) by peptide sequencing and immunoblot analysis. AP3 binds both inositol hexakisphosphate and preassembled cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…PLD is inhibited by endocytic proteins such as synaptojanin, AP180, and amphiphysin. Although AP180 and amphiphysin directly interact with PLD (50,51), the inhibition of PLD by synaptojanin is attributed to its ability to dephosphorylate PtdIns(4,5)P 2 (20,46), which is a cofactor for PLD (51).…”
Section: Discussionmentioning
confidence: 99%
“…PLD is inhibited by endocytic proteins such as synaptojanin, AP180, and amphiphysin. Although AP180 and amphiphysin directly interact with PLD (50,51), the inhibition of PLD by synaptojanin is attributed to its ability to dephosphorylate PtdIns(4,5)P 2 (20,46), which is a cofactor for PLD (51).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that synaptojanin and AP180 each inhibit PLD activity (21,22). We have now demonstrated that AmphI and AmphII each inhibit the activities of both PLD1 and PLD2 as a result of direct interaction with these enzymes.…”
Section: Discussionmentioning
confidence: 72%
“…Two such inhibitory proteins were purified to homogeneity and identified as synaptojanin and clathrin assembly protein 180 (AP180, previously named as clathrin assembly protein 3 or AP3) (21,22). The inhibition of PLD by synaptojanin was attributed to its ability to dephosphorylate PI(4,5)P 2 (21,23), whereas the inhibitory effect of AP180 is a result of its direct interaction with PLD (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several inhibitors of mammalian PLD have been identified. These inhibitors include fodrin (Lukowski et al, 1996), synaptojanin (Kim et al, 1996), and clathrin assembly protein (Lee et al, 1997), as well as several lipids including ceramide (Venable et al, 1996), alkylphosphate esters (Dittrich et al, 1996), and lysophosphatidyl-Ser (Kawabe et al, 1998). An intriguing observation indicated that oleate-dependent PLD from rat brain was inhibited by several acidic phospholipids, of which polyphosphatidylinositolbisphosphate (PIP 2 ) was the most effective inhibitor (Kanfer et al, 1996).…”
Section: Discussionmentioning
confidence: 99%